2015
DOI: 10.1007/s10459-014-9579-4
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting for values in healthcare: a preliminary review of the evidence

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. 9 Abstract Compassion, benevolence, respect and dignity are important for any healthcare 10 professional to ensure the provision of high quality care and patient outcomes. This paper 11 presents a structured search and thematic review of the research evidence relating to 12 values-based recruitment within healthcare. Several different databases, journals and 13 government reports were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 110 publications
(21 reference statements)
0
57
0
Order By: Relevance
“…Moreover, it is common practice in postgraduate medical settings internationally to combine measures of academic attainment and non-academic attributes in selection (Patterson et al 2015b(Patterson et al , 2016; however to date few researchers have empirically examined the complementary nature of these different selection methods in predicting in-role performance in practice (Prideaux et al 2011;Patterson et al 2016). The almost full range of scores achieved by successful applicants in this study provided a unique opportunity to address both of these areas of enquiry.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, it is common practice in postgraduate medical settings internationally to combine measures of academic attainment and non-academic attributes in selection (Patterson et al 2015b(Patterson et al , 2016; however to date few researchers have empirically examined the complementary nature of these different selection methods in predicting in-role performance in practice (Prideaux et al 2011;Patterson et al 2016). The almost full range of scores achieved by successful applicants in this study provided a unique opportunity to address both of these areas of enquiry.…”
Section: Discussionmentioning
confidence: 96%
“…high performing) academically, which can make differentiating between applicants on the basis of academic achievement challenging, and potentially inaccurate (McManus et al 2008). Conceptually, therefore, it appears necessary for non-academic attributes, in addition to academic attainment, to be assessed throughout physicians' medical career progression (Patterson et al 2015b). For this reason, in both undergraduate and postgraduate medical settings internationally, multi-method approaches to selection are increasingly used.…”
Section: Introductionmentioning
confidence: 99%
“…SEEG 2014;McLachlan 2010;Stratton and Elam 2014;Patterson et al 2015). Nonetheless, knowledge and evidence-based practice regarding selection of such attributes is undeniably in its embryonic stages in comparison to cognitive and academic assessments, which has over 100 years of research evidence behind it (e.g.…”
Section: How Can We Best Select For Important Personal Attributes Andmentioning
confidence: 99%
“…Elsewhere, researchers have focussed on values (e.g. Patterson et al 2015), integrity (Husbands et al 2015) and many other non-academic attributes and skills. MacKenzie et al (2016) paper in this special issue takes steps towards eliminating some of the attributes and traits that are not necessarily suitable to assess at the point of selection into medical school, as they are not found to be predictive of subsequent performance.…”
Section: How Can We Best Select For Important Personal Attributes Andmentioning
confidence: 99%
“…Research studies reported in medical education demonstrate a mixed response with some studies reporting a predictive correlation and others showing no correlation (Patterson et al . ). A surprising finding of our analysis was that scores for the personal statement, generally regarded as an unreliable measure on which to select applicants, were significantly positively correlated with results for three of the four in‐course modules.…”
Section: Discussionmentioning
confidence: 97%